Decreased humidity improves cognitive performance at extreme high indoor temperature - Tian, Xiaoyu; Fang, Zhaosong; Liu, Weiwei (Indoor air, 2021)
In this study, we examined the cognitive performance of subtropically acclimatized subjects at an extreme high indoor temperature and the effect of decreased humidity on the cognitive performance at the high temperature. Forty‐eight healthy subjects experienced the three exposure conditions: 26°C/relative humidity (RH) 70%, 39°C/RH50%, and 39°C/RH70% in a climate chamber. During 140‐minute‐long exposures to each thermal condition, they were required to perform cognitive tests that assess the perception, spatial orientation, concentration, memory, and thinking abilities. Meanwhile, their heart rate, core temperature, skin temperature, blood pressure, and body weight were measured and subjective responses, that is, thermal comfort, perceived air quality, and acute health symptoms were investigated. At the relative humidity of 70%, increasing indoor temperature from 26°C to 39°C caused a significant decrease in the accuracy of these cognitive tests. However, when the relative humidity decreased from 70% to 50% at 39°C, the accuracy of the cognitive tests increased significantly. Accordingly, the physiological and subjective responses of the subjects changed significantly with the changes in indoor temperature and humidity, which provided a basis to the variation in the cognitive performance. These results indicated that decreasing indoor humidity at extreme high temperature could improve the impaired cognitive performance.